Effectiveness of Guided Writing in Teaching Composition - Khatri, Dipendra Kumar (Journal of NELTA Surkhet, 2015)
This article summarizes the study conducted to find out the effectiveness of guided writing in teaching composition. Fifty-two students of grade nine studying at Khelnechour Secondary School, Surkhet were the sample population of this research. The researcher requested one of the teachers to involve in the practical teaching for carrying out the research. The tests (pre-test and post test) were the major tools for data collection. The students were ranked from the first to the fifty-second position based on the results of the pre-test. They were divided into two groups based on odd-even ranking of the individual scores. Then, experimental group was taught through guided writing activities whereas controlled group was taught without guided writing activities. Each groups attended thirty lessons. Then the post-test was administered. The results of these two tests (Pre and Post) were compared and found that guided writing activities were more effective in teaching composition. Journal of NELTA Surkhet Vol.4 2014: 18-25